Analysis and Implementation of an EMC-Based Radio Frequency Emission Measurement System - Ariyanto, Endro; Yudo, Yogi Anggun Saloko; Sailellah, Hassan Rizky Putra (Bahasa Indonesia, 2025)
The rapid advancement of electronic technology brings many benefits, but it also introduces risks of interference in the form of electromagnetic wave emissions that may affect the performance of nearby electronic devices. To ensure that devices maintain proper electromagnetic compatibility (EMC), precise and standardized methods for measuring radio-frequency emissions are required. This study focuses on developing radio-frequency emission measurement techniques and creating software capable of controlling a spectrum analyzer, displaying measurement results, storing data, and performing further analysis. The methods used follow the RTCA/DO-160C standard, covering both conducted and radiated emission measurements through voltage conversion and the application of device correction factors. Testing was carried out using a functional (black-box) approach on each main feature of the SpectrumAnalyzer object. The results demonstrate that all software functions operate correctly, from device initialization, data retrieval and storage, to spectrum normalization. Overall, the development and testing results confirm that the RFESW software is capable of performing radio-frequency emission measurements effectively and complies with the requirements of the RTCA/DO-160C standard.